Prática pedagógica em educação especial: inclusão de aluno com deficiência - Ferreira, Bárbara Mercedes Santiago (2016)
The process of inclusion of students with disabilities at school has triggered prospects for teacher training, the relationship teaching and learning and teaching practice. Thus there has been an exclusive assignment to the teacher who works directly with students with disabilities in establishing and ensuring the school inclusion prospects of access, retention and learning. From these considerations, the present study established the general objective analyze the perception of teachers who work in a special education school for the organization of their teaching in an inclusive perspective. To achieve the proposed goal we chose a qualitative approach by oportunizar a rich detail in the description of the collected data, the data analyzed in the light of Content Analysis (FRANCO, 2005). The choice of this method was due to the possibility of description, analysis and interpretation of messages and statements of all forms of speech, the social context of their production, the ideological influence and conceived with a great deal of meaning. The instrument used was the interview applied to five teachers who work at a special education school in one of Bahia within the municipality. This instrument allowed immediate capture and stream the desired information for the purpose of increasing the understanding of how teachers interpret the everyday aspects of their teaching experience in an inclusive perspective. The theoretical framework used as a subsidy for the development of the research was based on the sources of approaches (2000), Freire (2005), Januzzi (2012), Sacristan (1998), Stobäus and Mosquera (2012), which are based discussions about educational process of students with disabilities and how the teacher can organize their practice in an inclusive perspective. The study provided the presentation of the school setting of a special education unit and conflict and / or challenges faced by teachers of the institution. The analysis of the interviewees testimonies presented specific questions about the teacher look about disability and inclusion, teaching in Special Education and the repercussions of this in schools, especially in the teaching-learning. The accounts showed that there is a substantial gap between what needs to be done and what the teachers perform, but can develop activities that value the individuality of each student, respecting differences and seeking to place the student in various social contexts, in approximating family at school, for example.